Prosze z rozwiązaniami :

a. 2 x ( -3 ) + 6
b. -5 x ( - 8 )- 16
c. 2 x ( - 5 ) + 3 x ( - 2 )
d. 8 - 6 x ( - 5)
e. 6 - ( - 16 ) : ( - 8 )
f. ( 2 - 6 ) x ( - 8 )
g. -5 x ( -6 - 10 )
h. - 3 x ( - 1 ) - ( - 10 ) x 4
i. ( - 5 - 6 ) : ( - 11 )
j. 24 : ( -3 -5 )
k. ( - 8 + 30 ) : ( - 7 - 4 )

2

Odpowiedzi

2010-03-03T19:10:08+01:00
A.
2 x ( -3 ) + 6 =-6x+6=0


b.
-5 x ( - 8 )- 16=40-16=24

c.
2 x ( - 5 ) + 3 x ( - 2 )=-10-6=-16

d.
8 - 6 x ( - 5)=8+30=38

e.
6 - ( - 16 ) : ( - 8 )=6-2=4

f.
( 2 - 6 ) x ( - 8 )=-4*(-8)=32

g.
-5 x ( -6 - 10 ) =30+50=80

h.
- 3 x ( - 1 ) - ( - 10 ) x 4=3+40=43

i.
( - 5 - 6 ) : ( - 11 )=-11:(-11)=1

j.
24 : ( -3 -5 )=24:(-8)=-3

k.
( - 8 + 30 ) : ( - 7 - 4 )=22:(-11)=-2


POWODZENIA
Najlepsza Odpowiedź!
2010-03-03T19:10:18+01:00
A. 2 x ( -3 ) + 6
-6 + 6 = 0

b. -5 x ( - 8 )- 16
40 - 16 = 24

c. 2 x ( - 5 ) + 3 x ( - 2 )
-10 - 6 = (-16)

d. 8 - 6 x ( - 5)
8 + 30 = 38

e. 6 - ( - 16 ) : ( - 8 )
6 - 2 = 4

f. ( 2 - 6 ) x ( - 8 )
-4 * -8 = 32

g. -5 x ( -6 - 10 )
-5 * -16 = 80

h. - 3 x ( - 1 ) - ( - 10 ) x 4
3 - 40 = -37

i. ( - 5 - 6 ) : ( - 11 )
-11 : -11 = 1

j. 24 : ( -3 -5 )
24: -8 = -3

k. ( - 8 + 30 ) : ( - 7 - 4 )
22 : -11 = -2